Differential diagnosis of lung`s lesions in HIV-infected patients - N. O. Skorohodova; E. N. Raznatovskaya; R. N. Yasinskiy (Zaporožskij Medicinskij Žurnal)
Introduction. Occurring of intercurrent diseases in HIV-infected and AIDS patients depends on the state of cellular and humoral immunity, on the level of CD4 + cells, which is reduced to 300 cells/ml and it is determining factor for the occurrence of a secondary pathology. In Ukraine a co-infection: tuberculosis and HIV/AIDS – has a malignant character, it has an extremely unfavorable course and high numbers of deaths from primarily diagnosed tuberculosis.